2022
DOI: 10.3346/jkms.2022.37.e29
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effect of Hepatitis B Virus on COVID-19 Infected Patients: A Nationwide Population-Based Study Using the Health Insurance Review & Assessment Service Database

Abstract: Background Several studies have recently suggested that liver disease and cirrhosis were risk factors for poor outcomes in patients with coronavirus disease 2019 (COVID-19) infections. However, no large data study has reported the clinical course of COVID-19 patients with chronic hepatitis B virus (HBV) infections. This study investigated whether HBV infection had negative impacts on the clinical outcomes of COVID-19 patients. Methods We performed a nationwide populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Various studies have also investigated the relationship between anti-viral treatment for HBV and outcomes from SARS-CoV-2 infection. In a Korean retrospective study of 19,160 patients with COVID-19, Choe et al demonstrated that anti-viral treatment among HBV-infected patients was not associated with reduced mortality, hospitalisation stay, or rate of ICU admission compared to patients without antiviral therapy [ 44 ]. Of note, the antiviral-treated group showed higher proportion with progression to liver failure than their counterparts (4.3% vs. 1.3%; p = 0.032).…”
Section: Sars-cov-2 Infection On the Background Of Chronic Liver Diseasementioning
confidence: 99%
“…Various studies have also investigated the relationship between anti-viral treatment for HBV and outcomes from SARS-CoV-2 infection. In a Korean retrospective study of 19,160 patients with COVID-19, Choe et al demonstrated that anti-viral treatment among HBV-infected patients was not associated with reduced mortality, hospitalisation stay, or rate of ICU admission compared to patients without antiviral therapy [ 44 ]. Of note, the antiviral-treated group showed higher proportion with progression to liver failure than their counterparts (4.3% vs. 1.3%; p = 0.032).…”
Section: Sars-cov-2 Infection On the Background Of Chronic Liver Diseasementioning
confidence: 99%
“…Neither the degree of HBV replicative activity seems to affect the SARS-CoV-2 infection outcomes; inactive carriers or patients with previous infection have ALI and mortality rates comparable to patients with active hepatitis[ 57 , 58 ]. As further demonstration of the absence of correlation between HBV replicative activity and COVID-19-related outcomes, antiviral therapy for HBV is not able to determine a significant impact on mortality, need for admission to the ICU and hospitalization length[ 59 ]. Apparently, conflicting with these data, Yang et al [ 60 ] showed that the HBeAg-positive chronic HBV hepatitis are associated with a higher rate of hospitalization in ICU and mortality.…”
Section: Chronic Hepatitis and Covid-19 Clinical Outcomesmentioning
confidence: 99%
“…A study conducted in the United States reported that chronic hepatitis C in COVID-19 patients was associated with in-hospital mortality regardless of baseline comorbidities, admission values of laboratory tests, or liver damage induced by COVID-19[ 63 ]. The Korean nationwide population-based cohort study reported that after adjusting for age, sex, cirrhosis, and comorbidities, HBV infection itself appears not to influence the prognosis of COVID-19 patients[ 64 ].…”
Section: Covid-19 In Patients With Pre-existing Liver Diseasementioning
confidence: 99%